(untitled) (Scientia Agricola, 2009)
Phytoremediation is an attractive technique for soils contaminated with heavy metals, especially in conjunction with chelating agents to assist metal phytoextraction. Nevertheless, their studies in Brazil are rare. Thus, the objective of the present work was to evaluate the efficiency of the chelating agents EDDS and EDTA for the solubilization of heavy metals from two Oxisols contaminated by organic sources in Jaguariúna (LVJ) and inorganic sources in Paulínia (LVP), São Paulo State, Southeastern Brazil. First, the soil samples were fractionated and the DTPA method was used to quantify heavy metals available forms. The results indicated that the metals were highly available in the soil fractions and could be solubilized by the chelating agents. The soil was suspended for 24 h in a chelating agent solution (EDTA or EDDS) at rates of 0, 250, 500 and 750 mg kg-1 of soil. The concentration of solubilized heavy metals was determined in the resulting solution. The extent of metal solubilization varied according to soil type, the chelating agent added and the specific metal. The amount of iron solubilized, as compared to the total iron (LVJ) was 11% (EDTA) and 19% (EDDS). EDDS solubilized more Cu than EDTA in both soils but more Ni in LVJ, while EDTA solubilized more Zn in both soils but more Cd in LVP. Both EDTA and EDDS may be useful for phytoextraction from soils, although the iron content is an important factor regarding the phytoextraction of heavy metals with chelating agents in Oxisols.